Muslim Institutions of Higher Education in Postcolonial Africa - Lo, Mbaye; Haron, Muhammed (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
Muslim Institutions of Higher Education in Postcolonial Africa examines the colonial discriminatory practices against Muslim education through control and dismissal and discusses the education reform movement of the post-colonial experience.